2016
DOI: 10.1177/1078087416640126
|View full text |Cite
|
Sign up to set email alerts
|

Housing Disinvestment and Crime in a Phoenix Suburb: Exploring the Differential Effects of Investors and Owner-Occupants

Abstract: External investment in neighborhoods can inhibit crime. However, during the housing crisis, many investors were foreclosed upon, triggering large-scale community disinvestment. Yet the impact of this type of disinvestment on crime is currently unknown. Combining data on crime incidents with foreclosure, home sales, and sociodemographic data, this research assesses whether the foreclosure of properties owned by investors has an effect on crime in neighborhoods in Chandler, Arizona, a suburb in the heavily affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Studies find that homeowners, driven by a desire to protect the value of their financial investments, are more likely to maintain their properties, engage with their neighbors through social interaction or participation in community organizations, and demand services, while investors are more likely to defer maintenance, neglect their properties, and leave properties vacant (Galster 1983(Galster , 1987Hunter 1975;McCabe 2016;Rohe and Stewart 1996;Sampson and Raudenbush 2004;Travis 2019). Although homeowners' actions can exacerbate social exclusion and segregation (McCabe 2016), declines in neighborhood homeownership rates can lead to declines in neighborhood conditions, increased crime and disorder, disinvestment through out-migration and malaise among existing residents, and avoidance by potential residents (Chamberlain et al 2018;Geis and Ross 1998;Immergluck 2010;Perkins and Taylor 1996;Sampson and Raudenbush 2004). Extant research shows that neighborhood decline and disinvestment have negative implications for those living in these neighborhoods.…”
Section: Homeownership Neighborhood Stability and The Housing Crisismentioning
confidence: 99%
“…Studies find that homeowners, driven by a desire to protect the value of their financial investments, are more likely to maintain their properties, engage with their neighbors through social interaction or participation in community organizations, and demand services, while investors are more likely to defer maintenance, neglect their properties, and leave properties vacant (Galster 1983(Galster , 1987Hunter 1975;McCabe 2016;Rohe and Stewart 1996;Sampson and Raudenbush 2004;Travis 2019). Although homeowners' actions can exacerbate social exclusion and segregation (McCabe 2016), declines in neighborhood homeownership rates can lead to declines in neighborhood conditions, increased crime and disorder, disinvestment through out-migration and malaise among existing residents, and avoidance by potential residents (Chamberlain et al 2018;Geis and Ross 1998;Immergluck 2010;Perkins and Taylor 1996;Sampson and Raudenbush 2004). Extant research shows that neighborhood decline and disinvestment have negative implications for those living in these neighborhoods.…”
Section: Homeownership Neighborhood Stability and The Housing Crisismentioning
confidence: 99%
“…Foreclosure and vacancy are often precursors to residences that are demolished, and a recent and growing literature has found that foreclosure and vacancy are associated with crime and disorder (Arnio, Baumer, and Wolff 2012; Baumer, Wolff, and Arnio 2012; Boessan and Chamberlain 2017; Chamberlain et al 2018; Ellen, Lacoe, and Sharygin 2013; Lacoe and Ellen 2015; Lin and Walsh 2015; Spelman 1993; Wallace, Hedberg, and Katz 2012). Foreclosed and vacant properties are often considered a type of physical disorder in an urban neighborhood (Skogan 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent with prior research, we a priori examine the crime outcomes of part 1 violent, part 1 nonviolent, and computer-automated dispatch (CAD) incidents to test this hypothesis. Although the theoretical processes that we have described may impact all types of crime, it is common to examine differences across interpersonal crimes and property crimes (Boessan and Chamberlain 2017; Chamberlain et al 2018). Additionally, CAD incidents are examined, as these may capture other drug crimes or disorder events (Boggess and Maskaly 2014) that are commonly associated with problem vacant properties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 Foreclosures also offer visual indicators that neighborhoods are economically declining. This might occur by the presence of a large number of "for sale" signs in neighborhoods with a lot of foreclosures, or by signs of blight and disrepair as residents or investors abandon their homes (Chamberlain et al, 2018;Kingsley et al, 2009).…”
Section: Stressmentioning
confidence: 99%
“…The housing crisis dramatically increased neighborhood foreclosure rates and transformed many neighborhood structural conditions that may be relevant for IPV. Neighborhoods with more foreclosures experienced temporary increases in violent crime Cui & Walsh, 2015;Hipp & Chamberlain, 2015;Katz, Wallace, & Hedberg, 2013;Pfeiffer, Wallace, & Chamberlain, 2015), property crime (Arnio et al, 2012;Chamberlain, Wallace, Pfeiffer, & Gaub, 2018;Williams, Galster, & Verma, 2014), and even disorder (Wallace, Hedberg, & Katz, 2012). 1 Foreclosures also affected numerous other neighborhood conditions, such as residential change and mobility (Been, Ellen, Schwartz, Stiefel, & Weinstein, 2011), racially selective migration patterns (Hall, Crowder, & Spring, 2015;Pfeiffer & Lucio, 2015), and segregation (Hall et al, 2015;Hyra, Squires, Renner, & Kirk, 2013;Pfeiffer & Molina, 2013;Rugh & Massey, 2010), reshaping patterns of civic engagement (Estrada-Correa & Johnson, 2012;Pfeiffer & Morris, 2017;Weffer et al, 2014) and regional geographies of housing opportunity (Pfeiffer & Lucio, 2015).…”
Section: Introductionmentioning
confidence: 99%